Epoxy resin, epoxy resin composition, cured product thereof, and laminate

A specific epoxy resin composition with a long alkylene and polyether chain structure addresses flexibility and adhesion issues by providing a phase-separated structure that withstands thermal expansion differences and maintains adhesion across a wide temperature range.

JP7619080B2Active Publication Date: 2025-01-22DIC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021028404
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-24
Filing Date
2021-02-25
Publication Date
2025-01-22
Estimated Expiration
2041-02-25

AI Technical Summary

Technical Problem

Existing epoxy resins struggle to provide both flexibility and high adhesion, especially in applications where there are significant differences in thermal expansion between materials, leading to issues such as warping and stress accumulation.

Method used

A specific epoxy resin composition with a long alkylene chain and polyether chain structure, characterized by a phase-separated structure, which allows for both elastic deformation and high adhesion across a wide temperature range.

Benefits of technology

The composition provides a flexible cured product that can withstand thermal expansion differences, offering high adhesion and stress relaxation ability, maintaining performance over a wide temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619080000001
    Figure 0007619080000001
  • Figure 0007619080000002
    Figure 0007619080000002
  • Figure 0007619080000003
    Figure 0007619080000003
Patent Text Reader

Abstract

To provide a resin composition that gives a flexible cured product having sufficient flexibility to resist temperature change and deformation and high adhesion to withstand a thermal expansion difference of a base material, a novel epoxy resin suitably used for the composition, a cured product obtained by curing the resin composition, and a laminate having a layer composed of the cured product and a base material.SOLUTION: An epoxy resin represented by the formula (1) is used, where Ar is an aromatic ring.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an epoxy resin having a specific structure, a composition containing two types of epoxy resins, a cured product obtained by curing the composition, and a laminate having a layer made of the cured product. [Background technology]

[0002] As automobiles and airplanes continue to become lighter due to CO2 reductions and improved fuel efficiency, weight reductions are being made by reducing the number of spot welds and combining fiber-reinforced resins with metals, and there is a strong demand for higher performance adhesives for the structural materials used in these applications. In particular, when heat-bonding aluminum and fiber-reinforced resins, which have large differences in thermal expansion, the occurrence of warping and rippling due to interfacial stress associated with expansion and contraction is a problem, and adhesives that can alleviate this stress are required. Furthermore, with the advancement of electronic materials used in semiconductor encapsulation and insulating layers for multilayer printed circuit boards, warping due to the difference in thermal expansion between the silicon chip and the metal has become a serious problem due to the trend toward ultra-thin materials, and stress relaxation functions are now more important than ever before.

[0003] On the other hand, epoxy resins are widely used as adhesives because they have dimensional stability, electrical insulation, and chemical resistance when cured. However, maintaining high adhesive properties can lead to brittleness. Therefore, flexible epoxy resins have been disclosed, such as high-molecular-weight epoxy resins obtained by reacting liquid bisphenol A epoxy resins with aliphatic dicarboxylic acids such as dimer acid or sebacic acid as a molecular chain extender (see, for example, Patent Document 1), and high-molecular-weight epoxy resins derived from hydroxy compounds having aliphatic hydrocarbon groups (see Patent Document 2). However, because flexible epoxy resins have a plastic deformation mode, they are unable to repeatedly follow the differential expansion of the substrate while maintaining overall rigidity, resulting in durability issues.

[0004] Furthermore, epoxy resins that exhibit high elongation accompanied by elastic deformation generally have low glass transition temperatures, and while they have excellent flexibility and adhesive properties near the glass transition temperature, their adhesive strength drops significantly at high temperatures above the glass transition temperature. On the other hand, epoxy resins with high glass transition temperatures have low temperature dependence of adhesive strength, but they lack flexibility and do not have stress relaxation functions. For these reasons, there is a demand for epoxy resins that provide a flexible cured product that combines high elongation, which requires elastic deformation, with adhesive properties at room temperature and high temperatures. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 8-53533 [Patent Document 2] Japanese Patent Application Laid-Open No. 2006-335796 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide a resin composition that gives a flexible cured product that has both flexibility resistant to temperature changes and deformation and high adhesiveness that can withstand the thermal expansion difference of a substrate, a novel epoxy resin that can be suitably used with the composition, a cured product obtained by curing the resin composition, and a laminate comprising a layer of the cured product and a substrate. [Means for solving the problem]

[0007] As a result of extensive research, the present inventors have found that the above-mentioned problems can be solved by using an epoxy resin having a specific structure.

[0008] [ka] [In formula (1), each Ar independently represents a structure having an unsubstituted or substituted aromatic ring, X is a structural unit represented by the following general formula (2), and Y is a structural unit represented by the following general formula (3),

[0009] [ka] [In the formulas (2) and (3), Ar is the same as defined above, R1 and R2 each independently represent a hydrogen atom, a methyl group, or an ethyl group; R' is a divalent hydrocarbon group having 2 to 12 carbon atoms; R3, R4, R7, and R8 each independently represent a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group; R5, R6, R9, R 10 are each independently a hydrogen atom or a methyl group, n1 is an integer from 4 to 16, n2 is the average number of repeating units and is between 2 and 30. R 11 , R 12 are each independently a glycidyl ether group or a 2-methylglycidyl ether group, R 13 , R 14 each independently represents a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group, R 15 , R 16 is a hydrogen atom or a methyl group, p1, p2, and q are the average values ​​of the repetitions, p1 and p2 each independently represent a number from 0 to 5; and q is 0.5 to 5. However, the bond between X represented by the general formula (2) and Y represented by the general formula (3) may be random or block, and the total number of structural units X and Y present in one molecule is m1 and m2, respectively. An epoxy resin represented by the formula: An epoxy resin (a1) in which 1≦m1≦25 and 1≦m2≦25, or an epoxy resin (A) having an epoxy equivalent of 500 to 10,000 g / eq, comprising, as essential components, an epoxy resin (a2) satisfying 1≦m1≦25 and m2=0 and an epoxy resin (a3) ​​satisfying m1=0 and 1≦m2≦25; Epoxy resin (B) with an epoxy equivalent of 100 to 300 g / eq, The present invention provides an epoxy resin composition comprising:

[0010] The present invention also provides a cured product of the epoxy resin composition, and a laminate having a layer made of the cured product.

[0011] Furthermore, the present invention relates to a compound represented by the following general formula (5):

[0012] [ka] [In formula (5), each Ar independently represents a structure having an unsubstituted or substituted aromatic ring, X is a structural unit represented by the following general formula (2), and Y is a structural unit represented by the following general formula (3),

[0013] [ka] [In the formulas (2) and (3), Ar is the same as defined above, R1 and R2 each independently represent a hydrogen atom, a methyl group, or an ethyl group; R' is a divalent hydrocarbon group having 2 to 12 carbon atoms; R3, R4, R7, and R8 each independently represent a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group; R5, R6, R9, R 10 are each independently a hydrogen atom or a methyl group, n1 is an integer from 4 to 16, n2 is the average number of repeating units and is between 2 and 30. R 11 , R 12 are each independently a glycidyl ether group or a 2-methylglycidyl ether group, R 13 , R 14 each independently represents a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group, R 15 , R 16 is a hydrogen atom or a methyl group, p1, p2, and q are the average values ​​of the repetitions, p1 and p2 each independently represent a number from 0 to 5; and q is 0.5 to 5. However, the bond between X represented by the general formula (2) and Y represented by the general formula (3) may be random or block, and the total number of structural units X and Y present in one molecule is m1 and m2, respectively. An epoxy resin represented by the formula: The present invention provides an epoxy resin characterized by satisfying the conditions 1≦m1≦25 and 1≦m2≦25 and having an epoxy equivalent of 500 to 10,000 g / eq. [Effects of the Invention]

[0014] The epoxy resin of the present invention, which contains a long-chain alkylene chain and a polyether chain, can provide a flexible cured product that has both high elongation assuming elastic deformation and high adhesion that can withstand the thermal expansion difference of the substrate. Furthermore, the composition of the present invention can provide a cured product having a phase-separated structure that achieves both adhesion and stress relaxation ability and exhibits high adhesion over a wide temperature range. DETAILED DESCRIPTION OF THE INVENTION

[0015] The present invention relates to a compound represented by the following general formula (1):

[0016] [ka] [In formula (1), each Ar independently represents a structure having an unsubstituted or substituted aromatic ring, X is a structural unit represented by the following general formula (2), and Y is a structural unit represented by the following general formula (3),

[0017] [ka] [In the formulas (2) and (3), Ar is the same as defined above, R1 and R2 each independently represent a hydrogen atom, a methyl group, or an ethyl group; R' is a divalent hydrocarbon group having 2 to 12 carbon atoms; R3, R4, R7, and R8 each independently represent a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group; R5, R6, R9, R 10 are each independently a hydrogen atom or a methyl group, n1 is an integer from 4 to 16, n2 is the average number of repeating units and is between 2 and 30. R 11 , R 12 are each independently a glycidyl ether group or a 2-methylglycidyl ether group, R 13 , R 14 each independently represents a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group, R 15 , R 16 is a hydrogen atom or a methyl group, p1, p2, and q are the average values ​​of the repetitions, p1 and p2 each independently represent a number from 0 to 5; and q is 0.5 to 5. However, the bond between X represented by the general formula (2) and Y represented by the general formula (3) may be random or block, and the total number of structural units X and Y present in one molecule is m1 and m2, respectively. An epoxy resin represented by the formula: An epoxy resin (a1) in which 1≦m1≦25 and 1≦m2≦25, or an epoxy resin (A) having an epoxy equivalent of 500 to 10,000 g / eq, comprising, as essential components, an epoxy resin (a2) satisfying 1≦m1≦25 and m2=0 and an epoxy resin (a3) ​​satisfying m1=0 and 1≦m2≦25; Epoxy resin (B) with an epoxy equivalent of 100 to 300 g / eq, The epoxy resin composition is characterized by comprising:

[0018] <Epoxy resin (A)> The epoxy resin (A) used in the present invention is characterized in that it essentially contains an epoxy resin (a1) having the structural unit X represented by formula (2) and the structural unit Y represented by formula (3) and has an epoxy equivalent of 500 to 10,000 g / eq, or it uses an epoxy resin (a2) having the structural unit X represented by formula (2) in combination with an epoxy resin (a3) ​​having the structural unit (Y) represented by formula (3), and the epoxy equivalent of the mixture thereof is 500 to 10,000 g / eq. In this case, the bonding form between the structural unit X and the structural unit Y in the epoxy resin (a1) is not particularly limited and may be random or block, and the total number of each structural unit present in one molecule is m1 and m2, respectively.

[0019] In the present invention, by using an epoxy resin (A) having such a specific structure, the cured product thereof contains a structure derived from the long-chain alkylene chain of the structural unit X, and therefore has flexibility and can follow the thermal expansion difference of the substrate. Furthermore, since the epoxy resin composition contains a structure derived from the polyether chain in the structural unit Y, the viscosity of the epoxy resin (A) is kept low, improving workability in coating molding and the like.

[0020] Hereinafter, the exemplified structures and preferred structures of the common portions of the epoxy resins (a1), (a2), and (a3) ​​will be described without distinction, since they are the same. In the general formulas (1), (2), and (3), Ar each independently represents a structure having an unsubstituted or substituted aromatic ring. Examples of the aromatic ring include a benzene ring, a naphthalene ring, an anthracene ring, a phenanthrene ring, and a fluorene ring. Ar, which is a structure having such an aromatic ring, preferably represents a structure represented by the following formula (4):

[0021] [ka] ···(4)

[0022] In formula (4), the aromatic ring may be substituted or unsubstituted, and * represents the point of attachment.

[0023] In addition, in the general formulae (1), (2), and (3), structures represented by the following formulae are also included as Ar.

[0024] [ka]

[0025] In the formula, the aromatic ring may be substituted or unsubstituted, n=1 to 4, and * represents a point of attachment.

[0026] The aromatic ring of Ar may be substituted or unsubstituted. When Ar has a substituent, the substituent preferably includes an alkyl group, a halogen atom, a glycidyl ether group, a 2-methylglycidyl ether group, etc. Preferably, Ar is unsubstituted, or an alkyl group and a glycidyl ether group, or a 2-methylglycidyl ether group. Preferably, the number of substituents per aromatic ring is two or less, more preferably one or less, and particularly preferably unsubstituted.

[0027] The following structures are particularly preferred for Ar.

[0028] [ka]

[0029] Particularly preferred structures for Ar having a substituent include the following structures.

[0030] [ka]

[0031] In the structural unit X, the repeating unit n1 is an integer of 4 to 16. When n1 is 4 or more, the adhesive strength is improved and the deformation mode of the cured product is elastic deformation. Furthermore, when n1 is 16 or less, a decrease in crosslink density can be suppressed. It is preferably 4 to 12, and more preferably 6 to 12.

[0032] In the structural unit X, R1 and R2 each independently represent a hydrogen atom, a methyl group, or an ethyl group, R3 and R4 each independently represent a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group, and R5 and R6 each independently represent a hydrogen atom or a methyl group. Among these, R3 and R4 are preferably hydroxyl groups, and R5 and R6 are preferably hydrogen atoms.

[0033] In the structural unit Y, the repeating unit n2 has an average value of 2 to 30. This range is preferable because it provides a good balance between resin viscosity and crosslink density. It is preferably 2 to 25, and more preferably 4 to 20.

[0034] In the structural unit Y, R' represents a divalent hydrocarbon group having 2 to 12 carbon atoms. Within this range, the adhesive strength is improved and the deformation mode of the cured product is elastic. Preferably, R' is a divalent hydrocarbon group having 2 to 6 carbon atoms.

[0035] Examples of the divalent hydrocarbon group include a linear or branched alkylene group, an alkenylene group, an alkynylene group, a cycloalkylene group, an arylene group, and an aralkylene group (a divalent group having an alkylene group and an arylene group).

[0036] Examples of the alkylene group include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, a hexylene group, a trimethylene group, a tetramethylene group, a pentamethylene group, and a hexamethylene group. Examples of the alkenylene group include a vinylene group, a 1-methylvinylene group, a propenylene group, a butenylene group, and a pentenylene group. Examples of the alkynylene group include an ethynylene group, a propynylene group, a butynylene group, a pentynylene group, and a hexynylene group. Examples of the cycloalkylene group include a cyclopropylene group, a cyclobutylene group, a cyclopentylene group, and a cyclohexylene group. Examples of the arylene group include a phenylene group, a tolylene group, a xylylene group, and a naphthylene group.

[0037] Among these, ethylene, propylene and tetramethylene groups are preferred from the viewpoint of the balance between the availability of raw materials, the viscosity of the resulting epoxy resin (A), and the flexibility of the cured product.

[0038] In the structural unit Y, R7 and R8 each independently represent a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group, and R9 and R 10 Each of R7 and R8 independently represents a hydrogen atom or a methyl group. Among these, R7 and R8 are preferably a hydroxyl group, and R9 and R 10 is preferably a hydrogen atom.

[0039] In addition, R in the general formula (1) 11 , R 12 are each independently a glycidyl ether group or a 2-methylglycidyl ether group, and R 13 , R 14 are each independently a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group, and R 15 , R 16 is a hydrogen atom or a methyl group, p1, p2, and q are the average values ​​of the repeating groups, p1 and p2 are each independently 0 to 5, and q is 0.5 to 5. Among these, R 11 , R 12 is preferably a glycidyl ether group, and R 13 , R 14 is preferably a hydroxyl group, and R15 , R 16 is preferably a hydrogen atom. Furthermore, p1 and p2 are preferably 0 to 2, and q is preferably 0.5 to 2.

[0040] Furthermore, the epoxy equivalent of the epoxy resin (A) used in the present invention is 500 to 10,000 g / eq. This range ensures an excellent balance between flexibility and crosslink density in the resulting cured product. From the viewpoint of ease of handling and a better balance between flexibility and crosslink density, the range of 600 to 8,000 g / eq is preferred, and the range of 800 to 5,000 g / eq is more preferred.

[0041] The epoxy resin (a1) of the present invention may have, for example, the following structure.

[0042] [ka]

[0043] [ka]

[0044] [ka]

[0045] [ka]

[0046] [ka]

[0047] [ka]

[0048] [ka]

[0049] [ka]

[0050] [ka]

[0051] [ka]

[0052] [ka]

[0053] [ka]

[0054] In the structural formulas (A-1) to (A-12), ran represents a random bond, G represents a glycidyl group, R' represents a divalent hydrocarbon group having 2 to 12 carbon atoms, n1 is an integer from 4 to 16, n2 represents the average value of the repeating units and is 2 to 30, p1, p2, and q represent the average value of the repeating units, p1 and p2 are each independently 0 to 5, q is 0.5 to 5, and 1≦m1≦25 and 1≦m2≦25. However, the repeating units present in the repeating units may be the same or different from each other.

[0055] Among the above structural formulas, it is most preferable to use those represented by structural formulas (A-1), (A-2), (A-3), (A-5), (A-7), (A-8), and (A-9) in order to obtain a cured product with a better balance of physical properties.

[0056] Among the epoxy resins (A), examples of the epoxy resin (a2) having the structural unit X include resins represented by the following structural formulas.

[0057] [ka]

[0058] [ka]

[0059] [ka]

[0060] [ka]

[0061] [ka]

[0062] [ka]

[0063] [ka]

[0064] [ka]

[0065] [ka]

[0066] [ka]

[0067] [ka]

[0068] [ka]

[0069] In the structural formulas (A-13) to (A-24), G is a glycidyl group, n1 is an integer of 4 to 16, p1, p2, and q are the average values ​​of the repeating units, p1 and p2 are each independently 0 to 5, q is 0.5 to 5, and 1≦m1≦25, provided that the repeating units present in the repeating units may be the same or different.

[0070] Among the above structural formulas, those represented by structural formulas (A-13), (A-14), (A-15), (A-17), (A-19), (A-20), and (A-21) are preferably used because they provide a better balance of physical properties of the resulting cured product.

[0071] Among the epoxy resins (A), examples of the epoxy resin (a3) ​​having the structural unit Y include resins represented by the following structural formulas.

[0072] [ka]

[0073] [ka]

[0074] [ka]

[0075] [ka]

[0076]

change

[0077]

change

[0078]

change

[0079]

change

[0080]

change

[0081]

change

[0082]

change

[0083]

change

[0084] In the structural formulas (A-25) to (A-36), G is a glycidyl group, R' is a divalent hydrocarbon group having 2 to 12 carbon atoms, n2 is the average value of the repeating units and is 2 to 30, p1, p2, and q are the average values ​​of the repeating units and are 1≦m2≦25, p1 and p2 are each independently 0 to 5, and q is 0.5 to 5. However, the repeating units present in the repeating units may be the same or different.

[0085] Among the above structural formulas, it is most preferable to use those represented by structural formulas (A-25), (A-26), (A-27), (A-29), (A-31), (A-32), and (A-33) because they provide a more excellent balance of physical properties of the resulting cured product.

[0086] The method for producing the epoxy resin (A) used in the present invention is not particularly limited, but a preferred method is, for example, to react a diglycidyl ether (x1) of a dihydroxy compound having an alkylene chain or a polyether chain with an aromatic hydroxy compound (x2) in a molar ratio (x1) / (x2) of 1 / 1.01 to 1 / 5.0 to obtain a hydroxy compound (corresponding to a precursor or intermediate of the epoxy resin (A)), which is then reacted with an epihalohydrin (x3) from the viewpoint of ease of raw material availability and reaction. In this case, the epoxy resin (a2) can be obtained by using the diglycidyl ether of a dihydroxy compound having an alkylene chain alone, the epoxy resin (a3) ​​can be obtained by using the diglycidyl ether of a dihydroxy compound having a polyether chain alone, and the epoxy resin (a1) can be obtained by using the diglycidyl ether of a dihydroxy compound having an alkylene chain and the diglycidyl ether of a dihydroxy compound having a polyether chain together.

[0087] Alternatively, the epoxy resin (a1) can be obtained by reacting the epoxy resin (a2) and the epoxy resin (a3) ​​obtained above with an aromatic hydroxy compound (x2).

[0088] The product obtained in the reaction of the diglycidyl ether (x1) of a dihydroxy compound having an alkylene chain or a polyether chain with an aromatic hydroxy compound (x2) to obtain a hydroxy compound may contain unreacted aromatic hydroxy compound (x2). In the synthesis of the epoxy resin (A) used in the present invention, the product may be directly subjected to the reaction with epihalohydrin (x3) in the next step, or the unreacted aromatic hydroxy compound (x2) may be removed. However, from the viewpoint of the balance between toughness and flexibility of the cured product obtained from the epoxy resin composition of the present invention containing the resulting epoxy resin (A), the abundance of unreacted aromatic hydroxy compound (x2) in the hydroxy compound to be subjected to the next step is preferably in the range of 0.1 to 30% by mass.

[0089] The method for removing the unreacted aromatic hydroxy compound (x2) is not particularly limited, and various methods can be used. Examples include column chromatography separation, which utilizes differences in polarity; fractional distillation, which utilizes differences in boiling points; and alkaline aqueous extraction, which utilizes differences in solubility in alkaline water. Among these, alkaline aqueous extraction is preferred in terms of efficiency because it does not involve thermal alteration. In this case, the organic solvent used to dissolve the target substance can be any organic solvent that is immiscible with water, such as toluene or methyl isobutyl ketone, but methyl isobutyl ketone is particularly preferred in terms of solubility with the target substance.

[0090] The diglycidyl ether (x1) of a dihydroxy compound having an alkylene chain or a polyether chain is not particularly limited. For example, examples of diglycidyl ethers having an alkylene chain include 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, 1,9-nonanediol diglycidyl ether, 1,11-undecanediol diglycidyl ether, 1,12-dodecanediol diglycidyl ether, 1,13-tridecanediol diglycidyl ether, 1,14-tetradecanediol diglycidyl ether, 1,15-pentadecanediol diglycidyl ether, 1,16-hexadecanediol diglycidyl ether, 2-methyl-1,11-undecanediol diglycidyl ether, 3-methyl-1,11-undecanediol diglycidyl ether, and 2,6,10-trimethyl-1,11-undecanediol diglycidyl ether. Examples of diglycidyl ethers having a polyether chain include polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, polypentamethylene glycol diglycidyl ether, polyhexamethylene glycol diglycidyl ether, and polyheptamethylene glycol diglycidyl ether. These may contain organic chlorine impurities produced during the glycidyl etherification of hydroxy compounds, or may contain organic chlorine such as 1-chloromethyl-2-glycidyl ether (chloromethyl form) represented by the following structure. These diglycidyl ethers may be used alone or in combination of two or more.

[0091] [ka]

[0092] Among these, it is preferable to use 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, 1,9-nonanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether, as they provide an excellent balance between flexibility and heat resistance of the resulting cured product.

[0093] Furthermore, by simultaneously reacting the aforementioned diglycidyl ether having an alkylene chain and the diglycidyl ether having a polyether chain with an aromatic hydroxy compound (x2), a hydroxy compound having both the structural unit X and the structural unit Y can be obtained, and by further reacting this with epihalohydrin (x3), an epoxy resin (A) having both the structural unit X and the structural unit Y can be obtained.

[0094] The aromatic hydroxy compound (x2) is not particularly limited, and examples thereof include dihydroxybenzenes such as hydroquinone, resorcinol, and catechol; trihydroxybenzenes such as pyrogallol, 1,2,4-trihydroxybenzene, and 1,3,5-trihydroxybenzene; triphenylmethane-type phenols such as 4,4',4"-trihydroxytriphenylmethane; dihydroxynaphthalenes such as 1,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, 1,5-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, and 2,6-dihydroxynaphthalene; tetrafunctional phenols such as 1,1'-methylenebis-(2,7-naphthalenediol), 1,1'-binaphthalene-2,2',7,7'-tetraol, and 1,1'-oxybis-(2,7-naphthalenediol) obtained by coupling reaction of dihydroxynaphthalenes; bisphenols such as bis(4-hydroxyphenyl)methane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, and 1,1-bis(4-hydroxyphenyl)-1-phenylethane, and bis(4-hydroxyphenyl)sulfone, 2,2'-biphenol, 4,4'-biphenol, (1,1'-biphenyl)-3,4-diol, 3,3'-dimethyl-(1,1'-biphenyl)-4,4'-diol, 3-methyl-(1,1'-biphenyl)-4,4'-diol, 3,3',5,5'-tetramethylbiphenyl-2,2'-diol, 3,3',5,5'-tetramethylbiphenyl-4,4'-diol, 5-methyl-(1,1'-biphenyl)-3,4'diol, 3'-methyl-(1,1'-biphenyl)-3,4'diol, 4'-methyl-(1,1'-biphenyl)-3,Examples of suitable phenolic compounds include biphenols such as 4'-diol, alicyclic structure-containing phenols such as polyadducts of phenol and dicyclopentadiene and polyadducts of phenol and terpene compounds, naphthols such as bis(2-hydroxy-1-naphthyl)methane and bis(2-hydroxy-1-naphthyl)propane, and so-called Xylok-type phenolic resins, which are condensation reaction products of phenol and phenylene dimethyl chloride or biphenylene dimethyl chloride. These may be used alone or in combination of two or more. Further examples include compounds in which the aromatic nucleus of each of the above compounds is substituted with a methyl group, t-butyl group, or halogen atom. The alicyclic structure-containing phenols and the Xylok-type phenolic resins may contain not only bifunctional components but also trifunctional or higher functional components. These compounds may be used as is in the present invention, or the bifunctional components may be isolated and used after purification using a column or other purification process.

[0095] Among these, bisphenols are preferred because they provide an excellent balance between flexibility and toughness when cured, and bis(4-hydroxyphenyl)methane and 2,2-bis(4-hydroxyphenyl)propane are particularly preferred because of their outstanding toughness-imparting properties. Furthermore, when emphasis is placed on the curability and heat resistance of the cured product, dihydroxynaphthalenes are preferred, and 2,7-dihydroxynaphthalene is particularly preferred because of its outstanding rapid curing properties. Furthermore, when emphasis is placed on the moisture resistance of the cured product, it is preferable to use a compound containing an alicyclic structure.

[0096] From the viewpoint of reaction efficiency, the reaction ratio of the diglycidyl ether (x1) of the dihydroxy compound having an alkylene chain or a polyether chain to the aromatic hydroxy compound (x2) is preferably (x1) / (x2) in the range of 1 / 1.01 to 1 / 5.0 (molar ratio), and more preferably (x1) / (x2) in the range of 1 / 1.02 to 1 / 3.0 (molar ratio).

[0097] The reaction between the diglycidyl ether (x1) of a dihydroxy compound having an alkylene chain or a polyether chain and the aromatic hydroxy compound (x2) is preferably carried out in the presence of a catalyst. Various catalysts can be used, including, for example, alkali (earth) metal hydroxides such as sodium hydroxide, potassium hydroxide, lithium hydroxide, and calcium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; phosphorus compounds such as triphenylphosphine; chlorides, bromides, and iodides such as DMP-30, DMAP, tetramethylammonium, tetraethylammonium, tetrabutylammonium, and benzyltributylammonium; quaternary ammonium salts such as chlorides, bromides, and iodides such as tetramethylphosphonium, tetraethylphosphonium, tetrabutylphosphonium, and benzyltributylphosphonium; tertiary amines such as triethylamine, N,N-dimethylbenzylamine, 1,8-diazabicyclo[5.4.0]undecene, and 1,4-diazabicyclo[2.2.2]octane; and imidazoles such as 2-ethyl-4-methylimidazole and 2-phenylimidazole. Two or more of these catalysts may be used in combination. Among these, sodium hydroxide, potassium hydroxide, triphenylphosphine, and DMP-30 are preferred because the reaction proceeds rapidly and the amount of impurities is effectively reduced. The amount of these catalysts used is not particularly limited, but it is preferable to use 0.0001 to 0.1 moles per mole of aromatic hydroxyl groups in the aromatic hydroxy compound (x2). The form of these catalysts is also not particularly limited, and they may be used in the form of an aqueous solution or in the form of a solid.

[0098] The reaction between the diglycidyl ether (x1) of a dihydroxy compound having an alkylene chain or a polyether chain and the aromatic hydroxy compound (x2) can be carried out in the absence of a solvent or in the presence of an organic solvent. Examples of organic solvents that can be used include methyl cellosolve, ethyl cellosolve, toluene, xylene, methyl isobutyl ketone, dimethyl sulfoxide, propyl alcohol, and butyl alcohol. The amount of the organic solvent used is usually 50 to 300% by mass, preferably 100 to 250% by mass, based on the total mass of the raw materials charged. These organic solvents can be used alone or in combination. The absence of a solvent is preferred to speed up the reaction, while the use of dimethyl sulfoxide is preferred to reduce impurities in the final product.

[0099] The reaction temperature for the reaction is typically 50 to 180°C, and the reaction time is typically 1 to 30 hours. A reaction temperature of 100 to 160°C is preferred to reduce impurities in the final product. If the resulting compound exhibits significant coloration, an antioxidant or a reducing agent may be added to suppress this. The antioxidant is not particularly limited, but examples thereof include hindered phenol compounds such as 2,6-dialkylphenol derivatives, divalent sulfur compounds, and phosphite ester compounds containing a trivalent phosphorus atom. The reducing agent is not particularly limited, but examples thereof include hypophosphorous acid, phosphorous acid, thiosulfuric acid, sulfurous acid, hydrosulfite, or salts thereof.

[0100] After completion of the reaction, the reaction mixture may be neutralized or washed with water until the pH reaches 3 to 7, preferably 5 to 7. The neutralization and washing may be carried out according to a conventional method. For example, when a basic catalyst is used, an acidic substance such as hydrochloric acid, sodium dihydrogen phosphate, p-toluenesulfonic acid, or oxalic acid may be used as a neutralizing agent. After neutralization or washing, the solvent may be distilled off under reduced pressure and heating, if necessary, and the product may be concentrated to obtain a hydroxy compound.

[0101] By using the glycidyl ether having an alkylene chain and the glycidyl ether having a polyether chain in combination, a hydroxy compound having both the structural unit X and the structural unit Y can be obtained. In this case, preferred structures include, for example, compounds represented by the following structural formula:

[0102] [ka]

[0103] [ka]

[0104] [ka]

[0105] [ka]

[0106] [ka]

[0107] [ka]

[0108] [ka]

[0109] [ka]

[0110] [ka]

[0111] [ka]

[0112] [ka]

[0113] [ka]

[0114] In each of the structural formulas above, ran represents a random bond, R' represents a divalent hydrocarbon group having 2 to 12 carbon atoms, n1 represents an integer of 4 to 16, n2 represents the average value of the repeating units and is 2 to 30, and 1≦m1≦25 and 1≦m2≦25, provided that the repeating units present in the repeating units may be the same or different.

[0115] Furthermore, by using the glycidyl ether having an alkylene chain as a raw material, a hydroxy compound having the structural unit X can be obtained. In this case, preferred structures include, for example, compounds represented by the following structural formula:

[0116] [ka]

[0117] [ka]

[0118] [ka]

[0119] [ka]

[0120] [ka]

[0121] [ka]

[0122] [ka]

[0123] [ka]

[0124] [ka]

[0125] [ka]

[0126] [ka]

[0127] [ka]

[0128] In each of the above structural formulas, n1 is an integer of 4 to 16, and 1≦m1≦25.

[0129] Furthermore, by using the glycidyl ether having the polyether chain as a raw material, a hydroxy compound having the structural unit Y can be obtained. In this case, preferred structures include, for example, compounds represented by the following structural formula:

[0130]

change

[0131]

change

[0132]

change

[0133]

change

[0134]

change

[0135]

change

[0136]

change

[0137]

change

[0138]

change

[0139]

change

[0140]

change

[0141] [ka]

[0142] In each of the structural formulas above, R' is a divalent hydrocarbon group having 2 to 12 carbon atoms, n2 is the average value of the repeating units and is 2 to 30, and 1≦m2≦25, provided that the repeating units present in the repeating units may be the same or different.

[0143] In the method for producing the epoxy resin (A), the method for the glycidyl etherification reaction of the precursor (intermediate) hydroxy compound obtained above is not particularly limited, and examples thereof include a method of reacting a phenolic hydroxyl group with epihalohydrin, a method of olefinating the phenolic hydroxyl group and then oxidizing the carbon-carbon double bond of the olefin with an oxidizing agent, etc. Among these, the method using epihalohydrin (x3) is preferred in terms of ease of raw material availability and reaction.

[0144] Examples of methods using epihalohydrin (x3) include adding 0.3 to 100 moles of epihalohydrin (x3) per mole of aromatic hydroxyl group of the hydroxy compound obtained above, and then reacting the mixture at a temperature of 20 to 120°C for 0.5 to 10 hours while adding 0.9 to 2.0 moles of a basic catalyst per mole of aromatic hydroxyl group of the hydroxy compound all at once or gradually. The greater the excess amount of epihalohydrin (x3), the closer the resulting epoxy resin will be to its theoretical structure, and the more effectively it can suppress the formation of secondary hydroxyl groups resulting from the reaction of unreacted aromatic hydroxyl groups with epoxy groups. From this perspective, a range of 2.5 to 100 equivalents is preferred. The basic catalyst may be a solid or an aqueous solution thereof. When an aqueous solution is used, it may be continuously added, and water and epihalohydrin (x3) may be continuously distilled from the reaction mixture under reduced pressure or under normal pressure, followed by liquid separation to remove water and continuously return epihalohydrin (x3) to the reaction mixture.

[0145] In industrial production, all of the epihalohydrin (x3) charged in the first batch of epoxy resin production is fresh, but from the next batch onwards, it is preferable to use a combination of epihalohydrin (x3) recovered from the crude reaction product and fresh epihalohydrin (x3) equivalent to the amount consumed and lost in the reaction. The epihalohydrin (x3) used in this case is not particularly limited, but examples include epichlorohydrin and epibromohydrin. Among these, epichlorohydrin is preferred due to its easy availability.

[0146] The basic catalyst is not particularly limited, and examples thereof include alkaline earth metal hydroxides, alkali metal carbonates, and alkali metal hydroxides. In particular, alkali metal hydroxides are preferred because of their excellent catalytic activity in the epoxy resin synthesis reaction, and examples thereof include sodium hydroxide and potassium hydroxide. When used, these alkali metal hydroxides may be used in the form of an aqueous solution of about 10 to 55 mass %, or may be used in solid form.

[0147] The use of an organic solvent in combination can also increase the reaction rate in the synthesis of the epoxy resin. Examples of such organic solvents include, but are not limited to, ketones such as acetone and methyl ethyl ketone; alcohols such as methanol, ethanol, 1-propyl alcohol, isopropyl alcohol, 1-butanol, secondary butanol, and tertiary butanol; cellosolves such as methyl cellosolve and ethyl cellosolve; ethers such as tetrahydrofuran, 1,4-dioxane, 1,3-dioxane, and diethoxyethane; and aprotic polar solvents such as acetonitrile, dimethyl sulfoxide, and dimethylformamide. These organic solvents may be used alone or in combination of two or more, as appropriate, to adjust the polarity.

[0148] The reaction product of these glycidylation reactions is washed with water, and then the unreacted epihalohydrin (x3) and any organic solvent used are removed by distillation under heating and reduced pressure. Furthermore, to obtain an epoxy resin with even less hydrolyzable halogen, the resulting epoxy resin can be dissolved again in an organic solvent such as toluene, methyl isobutyl ketone, or methyl ethyl ketone, and an aqueous solution of an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide can be added to further carry out the reaction. In this case, a phase transfer catalyst such as a quaternary ammonium salt or crown ether may be present to improve the reaction rate.

[0149] When a phase transfer catalyst is used, the amount thereof is preferably in the range of 0.1 to 3.0% by mass based on the epoxy resin used. After completion of the reaction, the salt formed is removed by filtration, washing with water, etc., and the solvent, such as toluene or methyl isobutyl ketone, is distilled off under heating and reduced pressure to obtain a high-purity epoxy resin.

[0150] The blending ratio of the epoxy resin (a2) and the epoxy resin (a3) ​​obtained above is not limited in any way other than that the epoxy equivalent of the mixture is in the range of 500 to 10,000 g / eq, and can be appropriately selected depending on the physical properties of the target cured product, etc. For example, the mass ratio of epoxy resin (a2) / epoxy resin (a3) ​​is preferably in the range of 20 / 80 to 80 / 20, and particularly preferably in the range of 30 / 70 to 70 / 30.

[0151] In the present invention, it is preferable that the cured product obtained by curing the epoxy resin composition has a phase-separated structure in order to impart greater flexibility to the cured product. From this viewpoint, the present invention is characterized in that the epoxy resin (A) is used in combination with an epoxy resin (B) having an epoxy equivalent of 100 to 300 g / eq.

[0152] The epoxy resin (B) may have an epoxy equivalent in the range of 100 to 300 g / eq, and its structure is not limited. Examples thereof include liquid epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AD ​​type epoxy resins, polyhydroxybenzene type epoxy resins, polyhydroxynaphthalene type epoxy resins, biphenyl type epoxy resins, and tetramethylbiphenyl type epoxy resins; brominated epoxy resins such as brominated phenol novolac type epoxy resins; solid bisphenol A type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, triphenylmethane type epoxy resins, tetraphenylethane type epoxy resins; and dicyclohexyl benzoate type epoxy resins. Examples of suitable epoxy resins include anthradiene-phenol addition reaction type epoxy resins, phenol aralkyl type epoxy resins, phenylene ether type epoxy resins, naphthylene ether type epoxy resins, naphthol novolac type epoxy resins, naphthol aralkyl type epoxy resins, naphthol-phenol co-condensed novolac type epoxy resins, naphthol-cresol co-condensed novolac type epoxy resins, aromatic hydrocarbon formaldehyde resin-modified phenol resin type epoxy resins, and biphenyl-modified novolac type epoxy resins. These may be used alone or in combination of two or more types, and it is preferable to select and use various types depending on the intended use, the physical properties of the cured product, etc.

[0153] Among these, it is preferable to use liquid epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AD ​​type epoxy resins, polyhydroxybenzene type epoxy resins, polyhydroxynaphthalene type epoxy resins, biphenyl type epoxy resins, and tetramethylbiphenyl type epoxy resins, and it is particularly preferable to use epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, and bisphenol AD ​​... the like, which have an epoxy equivalent of 100 to 300 g / eq.

[0154] In the present invention, the ratio of the epoxy resin (A) to the epoxy resin (B) is not particularly limited, but from the viewpoint of facilitating phase separation in the cured product, the mass ratio of the epoxy resin (A) to the epoxy resin (B), (A):(B), is 97:3 to 3:97, preferably 10:90 to 90:10, and particularly preferably 80:20 to 20:80. Phase separation in the cured product results in a sea-island structure, which allows the cured product to achieve both good adhesion and stress relaxation ability, exhibits high adhesive strength over a particularly wide temperature range, and has the effect of reducing the mold shrinkage rate before and after heat curing of the resin composition.

[0155] The phase-separated structure is formed spontaneously during the curing reaction based on the compatibility between the epoxy resin (A) and the epoxy resin (B). The phase-separated structure generally consists of resin particles with an average particle size of 10 nm to 100 μm and a surrounding matrix. The cured products that form the resin particles and the matrix are determined by their blending ratios, the type of curing agent, and the effect of the curing agent. In other words, either the resin particles contain a cured product of the epoxy resin (A) and the matrix contains a cured product of the epoxy resin (B), or the resin particles contain a cured product of the epoxy resin (B) and the matrix contains a cured product of the epoxy resin (A).

[0156] The phase separation structure of the cured product can be observed using a scanning electron microscope (SEM) or an atomic force microscope (AFM). If a sea-island structure is formed, the particle size of the islands can be measured. In the present invention, the average particle size of the resin particles is determined by randomly selecting 50 islands from the islands within a 200 μm × 260 μm field of view, measuring the particle sizes, and averaging the measurements. Furthermore, AFM observation can confirm the relative hardness distribution of the sea and island regions.

[0157] The epoxy resin composition of the present invention preferably further contains a curing agent (C) that is reactive with a general epoxy resin.

[0158] The curing agent (C) is not particularly limited, and examples thereof include amine compounds, acid anhydrides, amide compounds, phenolic hydroxyl group-containing compounds, carboxylic acid compounds, and hydroxy compounds that are precursors of the epoxy resin (A) described above.

[0159] Examples of the amine compound include aliphatic amine compounds such as trimethylenediamine, ethylenediamine, N,N,N',N'-tetramethylethylenediamine, pentamethyldiethylenetriamine, triethylenediamine, dipropylenediamine, N,N,N',N'-tetramethylpropylenediamine, tetramethylenediamine, pentanediamine, hexamethylenediamine, trimethylhexamethylenediamine, N,N,N',N'-tetramethylhexamethylenediamine, N,N-dimethylcyclohexylamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, dimethylaminopropylamine, diethylaminopropylamine, dibutylaminopropylamine, 1,4-diazabicyclo(2,2,2)octane(triethylenediamine), polyoxyethylenediamine, polyoxypropylenediamine, bis(2-dimethylaminoethyl)ether, dimethylaminoethoxyethoxyethanol, triethanolamine, and dimethylaminohexanol;

[0160] Alicyclic and heterocyclic amine compounds such as piperidine, piperazine, menthanediamine, isophoronediamine, methylmorpholine, ethylmorpholine, N,N',N"-tris(dimethylaminopropyl)hexahydro-s-triazine, 3,9-bis(3-aminopropyl)-2,4,8,10-tetraoxyspiro(5,5)undecane adduct, N-aminoethylpiperazine, trimethylaminoethylpiperazine, bis(4-aminocyclohexyl)methane, N,N'-dimethylpiperazine, 1,8-diazabicyclo-[5.4.0]-undecene (DBU), etc.

[0161] Aromatic amine compounds such as o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, benzylmethylamine, dimethylbenzylamine, m-xylylenediamine, pyridine, picoline, and α-methylbenzylmethylamine;

[0162] Examples of the modified amine compounds include epoxy compound-added polyamines, Michael addition polyamines, Mannich addition polyamines, thiourea addition polyamines, ketone-blocked polyamines, dicyandiamide, guanidine, organic acid hydrazides, diaminomaleonitrile, aminimide, boron trifluoride-piperidine complex, and boron trifluoride-monoethylamine complex.

[0163] Examples of the acid anhydride include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, maleic anhydride polypropylene glycol, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride.

[0164] Examples of the phenolic hydroxyl group-containing compound include polyhydric phenol compounds such as phenol novolac resin, cresol novolac resin, aromatic hydrocarbon formaldehyde resin-modified phenolic resin, dicyclopentadiene phenol adduct resin, phenol aralkyl resin (Xyloc resin), naphthol aralkyl resin, trimethylolmethane resin, tetraphenylolethane resin, naphthol novolac resin, naphthol-phenol co-condensed novolac resin, naphthol-cresol co-condensed novolac resin, biphenyl-modified phenolic resin (a polyhydric phenol compound in which phenol nuclei are linked via bismethylene groups), biphenyl-modified naphthol resin (a polyhydric naphthol compound in which phenol nuclei are linked via bismethylene groups), aminotriazine-modified phenolic resin (a polyhydric phenol compound in which phenol nuclei are linked via melamine, benzoguanamine, or the like), and alkoxy group-containing aromatic ring-modified novolac resin (a polyhydric phenol compound in which phenol nuclei and alkoxy group-containing aromatic rings are linked via formaldehyde).

[0165] Examples of the amide compounds include dicyandiamide and polyamidoamine, etc. Examples of the polyamidoamine include those obtained by reacting an aliphatic dicarboxylic acid such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, or azelaic acid, or a carboxylic acid compound such as a fatty acid or dimer acid, with an aliphatic polyamine or a polyamine having a polyoxyalkylene chain.

[0166] Examples of the carboxylic acid compound include carboxylic acid polymers such as carboxylic acid-terminated polyester, polyacrylic acid, and maleic acid-modified polypropylene glycol.

[0167] When using these curing agents, only one type of curing agent may be used, or two or more types may be mixed. For applications such as underfill materials and general coating applications, it is preferable to use the amine-based compounds, carboxylic acid-based compounds, and / or acid anhydride-based compounds. For applications such as adhesives and flexible wiring boards, amine-based compounds, particularly dicyandiamide, are preferred in terms of workability, curability, and long-term stability. For applications as semiconductor encapsulation materials, solid phenol-based compounds are preferred in terms of the heat resistance of the cured product.

[0168] The resin composition of the present invention may contain resins other than the epoxy resin (A) and the epoxy resin (B) as long as the effects of the present invention are not impaired.

[0169] <Other epoxy resins> The resin composition of the present invention may contain other epoxy resins in addition to the epoxy resin (A) and the epoxy resin (B) as long as the effects of the present invention are not impaired. In this case, the total amount of the epoxy resin (A) and the epoxy resin (B) in the composition of the present invention is preferably 30% by mass or more, and particularly preferably 40% by mass or more, of the total epoxy resins.

[0170] The epoxy resins that can be used in combination are not limited in any way as long as they do not belong to the epoxy resin (A) and the epoxy resin (B), and examples thereof include liquid epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AD ​​type epoxy resins, polyhydroxybenzene type epoxy resins, polyhydroxynaphthalene type epoxy resins, biphenyl type epoxy resins, and tetramethylbiphenyl type epoxy resins; brominated epoxy resins such as brominated phenol novolac type epoxy resins; solid bisphenol A type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins; and triphenylmethane type epoxy resins, tetraphenylethane type epoxy resins, dicyclopentadiene-phenol addition reaction type epoxy resins, phenol aralkyl type epoxy resins, phenylene ether type epoxy resins, naphthylene ether type epoxy resins, naphthol novolac type epoxy resins, naphthol aralkyl type epoxy resins, naphthol-phenol co-condensed novolac type epoxy resins, naphthol-cresol co-condensed novolac type epoxy resins, aromatic hydrocarbon formaldehyde resin-modified phenolic resin type epoxy resins, biphenyl-modified novolac type epoxy resins, and the like. These may be used alone or in combination of two or more types, and it is preferable to select and use various types depending on the intended use, the physical properties of the cured product, and the like.

[0171] The amounts of epoxy resin and curing agent in the composition of the present invention are not particularly limited, but in terms of good mechanical properties of the resulting cured product, it is preferable that the amount of active groups in the curing agent be 0.4 to 1.5 equivalents per total equivalent of epoxy groups in the total amount of epoxy resins including epoxy resin (A) and epoxy resin (B).

[0172] <Curing accelerator> The epoxy resin composition of the present invention may contain a curing accelerator. Various curing accelerators can be used, including urea compounds, phosphorus-based compounds, tertiary amines, imidazole, organic acid metal salts, Lewis acids, and amine complex salts. When used as an adhesive, urea compounds, particularly 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU), are preferred due to their excellent workability and low-temperature curing properties. When used as a semiconductor encapsulating material, triphenylphosphine is a preferred phosphorus-based compound, and 1,8-diazabicyclo-[5.4.0]-undecene is a preferred tertiary amine due to their excellent curability, heat resistance, electrical properties, and moisture resistance reliability.

[0173] <Filler> The epoxy resin composition of the present invention may further contain a filler. Examples of the filler include inorganic fillers and organic fillers. Examples of the inorganic filler include inorganic fine particles.

[0174] Examples of inorganic fine particles include those with excellent heat resistance such as alumina, magnesia, titania, zirconia, and silica (quartz, fumed silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, and ultrafine amorphous silica); those with excellent thermal conductivity such as boron nitride, aluminum nitride, alumina oxide, titanium oxide, magnesium oxide, zinc oxide, silicon oxide, and diamond; those with excellent electrical conductivity such as metal fillers and / or metal-coated fillers using metals or alloys (e.g., iron, copper, magnesium, aluminum, gold, silver, platinum, zinc, manganese, and stainless steel); and those with excellent barrier properties such as minerals such as mica, clay, kaolin, talc, zeolite, wollastonite, and smectite, as well as potassium titanate, magnesium sulfate, sepiolite, and zonolite. those with a high refractive index include barium titanate, zirconia oxide, titanium oxide, etc.; those exhibiting photocatalytic properties include photocatalytic metals such as titanium, cerium, zinc, copper, aluminum, tin, indium, phosphorus, carbon, sulfur, ruthenium, nickel, iron, cobalt, silver, molybdenum, strontium, chromium, barium, and lead, composites of these metals, and oxides thereof; those with excellent abrasion resistance include metals such as silica, alumina, zirconia, and magnesium oxide, and composites and oxides thereof; those with excellent conductivity include metals such as silver and copper, tin oxide, and indium oxide; those with excellent insulation properties include silica, etc.; and those with excellent UV blocking properties include titanium oxide and zinc oxide, etc.

[0175] These inorganic fine particles may be selected appropriately depending on the application, and may be used alone or in combination of two or more kinds. In addition, the inorganic fine particles have various properties in addition to the properties exemplified above, so that they may be selected appropriately depending on the application.

[0176] For example, when silica is used as inorganic fine particles, there is no particular limitation, and known silica fine particles such as powdered silica or colloidal silica can be used. Commercially available powdered silica fine particles include, for example, Aerosil 50 and 200 manufactured by Nippon Aerosil Co., Ltd., Sildex H31, H32, H51, H52, H121, and H122 manufactured by Asahi Glass Co., Ltd., E220A and E220 manufactured by Nippon Silica Industry Co., Ltd., SYLYSIA470 manufactured by Fuji Silysia Co., Ltd., and SG Flake manufactured by Nippon Sheet Glass Co., Ltd.

[0177] Examples of commercially available colloidal silica include methanol silica sol, IPA-ST, MEK-ST, NBA-ST, XBA-ST, DMAC-ST, ST-UP, ST-OUP, ST-20, ST-40, ST-C, ST-N, ST-O, ST-50, and ST-OL, all of which are manufactured by Nissan Chemical Industries, Ltd.

[0178] Surface-modified silica fine particles may also be used, for example, the silica fine particles that have been surface-treated with a reactive silane coupling agent having a hydrophobic group, or modified with a compound having a (meth)acryloyl group. Examples of commercially available powdered silica modified with a compound having a (meth)acryloyl group include Aerosil RM50, R711, etc. manufactured by Nippon Aerosil Co., Ltd., and examples of commercially available colloidal silica modified with a compound having a (meth)acryloyl group include MIBK-SD, etc. manufactured by Nissan Chemical Industries, Ltd.

[0179] The shape of the silica fine particles is not particularly limited, and spherical, hollow, porous, rod-like, plate-like, fibrous, or irregularly shaped particles can be used. The primary particle diameter is preferably in the range of 5 to 200 nm. If the particle diameter is less than 5 nm, the inorganic fine particles will not be sufficiently dispersed in the dispersion, and if the particle diameter exceeds 200 nm, the cured product may not maintain sufficient strength.

[0180] Titanium oxide microparticles can be used not only as extender pigments but also as ultraviolet light-responsive photocatalysts, such as anatase titanium oxide, rutile titanium oxide, and brookite titanium oxide. Furthermore, particles designed to respond to visible light by doping different elements into the crystalline structure of titanium oxide can also be used. Suitable elements for doping titanium oxide include anionic elements such as nitrogen, sulfur, carbon, fluorine, and phosphorus, and cationic elements such as chromium, iron, cobalt, and manganese. The titanium oxide can be used in the form of a powder, a sol dispersed in an organic solvent or water, or a slurry. Commercially available powdered titanium oxide microparticles include, for example, Aerosil P-25 manufactured by Nippon Aerosil Co., Ltd. and ATM-100 manufactured by Teika Co., Ltd. Commercially available slurry-type titanium oxide microparticles include, for example, TKD-701 manufactured by Teika Co., Ltd.

[0181] <Fiber matrix> The resin composition of the present invention may further contain a fibrous substrate. The fibrous substrate of the present invention is not particularly limited, but is preferably one used in fiber-reinforced resins, such as inorganic fibers and organic fibers.

[0182] Examples of inorganic fibers include inorganic fibers such as carbon fibers, glass fibers, boron fibers, alumina fibers, and silicon carbide fibers, as well as carbon fibers, activated carbon fibers, graphite fibers, tungsten carbide fibers, silicon carbide fibers (silicon carbide fibers), ceramic fibers, natural fibers, mineral fibers such as basalt, boron nitride fibers, boron carbide fibers, and metal fibers. Examples of the metal fibers include aluminum fibers, copper fibers, brass fibers, stainless steel fibers, and steel fibers.

[0183] Examples of organic fibers include synthetic fibers made from resin materials such as polybenzazole, aramid, PBO (polyparaphenylene benzoxazole), polyphenylene sulfide, polyester, acrylic, polyamide, polyolefin, polyvinyl alcohol, and polyarylate; natural fibers such as cellulose, pulp, cotton, wool, and silk; and regenerated fibers such as protein, polypeptide, and alginic acid.

[0184] Among these, carbon fiber and glass fiber are preferred because they have a wide range of industrial applications. Of these, only one type may be used, or two or more types may be used simultaneously.

[0185] The fibrous substrate of the present invention may be an assembly of fibers, with continuous or discontinuous fibers, and may be in the form of a woven or nonwoven fabric. It may also be a fiber bundle in which fibers are aligned in one direction, or a sheet in which fiber bundles are arranged. It may also be a three-dimensional shape in which a thickness is added to an assembly of fibers.

[0186] <Dispersion medium> The resin composition of the present invention may contain a dispersion medium for the purpose of adjusting the solid content and viscosity of the resin composition. The dispersion medium may be any liquid medium that does not impair the effects of the present invention, and examples of the dispersion medium include various organic solvents and liquid organic polymers.

[0187] Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone (MEK), and methyl isobutyl ketone (MIBK); cyclic ethers such as tetrahydrofuran (THF) and dioxolane; esters such as methyl acetate, ethyl acetate, and butyl acetate; aromatics such as toluene and xylene; and alcohols such as carbitol, cellosolve, methanol, isopropanol, butanol, and propylene glycol monomethyl ether. These can be used alone or in combination, but methyl ethyl ketone is preferred from the standpoint of volatility during coating and solvent recovery.

[0188] The liquid organic polymer is a liquid organic polymer that does not directly contribute to the curing reaction, and examples thereof include modified carboxyl group-containing polymers (Floren G-900, NC-500: Kyoeisha), acrylic polymers (Floren WK-20: Kyoeisha), amine salts of special modified phosphate esters (HIPLAAD ED-251: Kusumoto Chemical), and modified acrylic block copolymers (DISPERBYK2000; BYK-Chemie).

[0189] <Resin> The resin composition of the present invention may contain a resin other than the various compounds of the present invention described above. As the resin, any known and commonly used resin may be blended as long as it does not impair the effects of the present invention, and for example, a thermosetting resin or a thermoplastic resin may be used.

[0190] Thermosetting resins are resins that can become substantially insoluble and infusible when cured by heat, radiation, or catalysts. Examples include phenolic resins, urea resins, melamine resins, benzoguanamine resins, alkyd resins, unsaturated polyester resins, vinyl ester resins, diallyl terephthalate resins, silicone resins, urethane resins, furan resins, ketone resins, xylene resins, thermosetting polyimide resins, benzoxazine resins, active ester resins, aniline resins, cyanate ester resins, styrene-maleic anhydride (SMA) resins, and maleimide resins. These thermosetting resins can be used alone or in combination.

[0191] Thermoplastic resins refer to resins that can be melt-molded by heating. Specific examples include polyethylene resins, polypropylene resins, polystyrene resins, rubber-modified polystyrene resins, acrylonitrile-butadiene-styrene (ABS) resins, acrylonitrile-styrene (AS) resins, polymethyl methacrylate resins, acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polyethylene terephthalate resins, ethylene vinyl alcohol resins, cellulose acetate resins, ionomer resins, polyacrylonitrile resins, polyamide resins, polyacetal resins, polybutylene terephthalate resins, polylactic acid resins, polyphenylene ether resins, modified polyphenylene ether resins, polycarbonate resins, polysulfone resins, polyphenylene sulfide resins, polyetherimide resins, polyethersulfone resins, polyarylate resins, thermoplastic polyimide resins, polyamideimide resins, polyetheretherketone resins, polyketone resins, liquid crystal polyester resins, fluororesins, syndiotactic polystyrene resins, and cyclic polyolefin resins. These thermoplastic resins can be used alone or in combination of two or more.

[0192] <Other compounds> The resin composition of the present invention may contain other compounds, such as catalysts, polymerization initiators, inorganic pigments, organic pigments, extender pigments, clay minerals, waxes, surfactants, stabilizers, flow modifiers, coupling agents, dyes, leveling agents, rheology control agents, ultraviolet absorbers, antioxidants, flame retardants, plasticizers, and reactive diluents.

[0193] <Cured product> The resin composition of the present invention can be cured to obtain a cured product. The curing can be carried out at room temperature or by heating. A known and commonly used curing catalyst may be used for curing. When heat curing is performed, the composition may be cured by a single heating step or may be cured through multiple heating steps.

[0194] When a curing catalyst is used, examples thereof include inorganic acids such as hydrochloric acid, sulfuric acid, and phosphoric acid; organic acids such as p-toluenesulfonic acid, monoisopropyl phosphate, and acetic acid; inorganic bases such as sodium hydroxide and potassium hydroxide; titanate esters such as tetraisopropyl titanate and tetrabutyl titanate; and various chemical compounds containing basic nitrogen atoms such as 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), 1,4-diazabicyclo[2.2.2]octane (DABCO), tri-n-butylamine, dimethylbenzylamine, monoethanolamine, imidazole, 2-ethyl-4-methyl-imidazole, 1-methylimidazole, and N,N-dimethyl-4-aminopyridine (DMAP). Examples of catalysts that can be used include: quaternary ammonium salts such as tetramethylammonium salts, tetrabutylammonium salts, and dilauryldimethylammonium salts, which have chloride, bromide, carboxylate, or hydroxide as a counter anion; tin carboxylates such as dibutyltin diacetate, dibutyltin dioctoate, dibutyltin dilaurate, dibutyltin diacetylacetonate, tin octoate, and tin stearate; and organic peroxides such as benzoyl peroxide, cumene hydroperoxide, dicumyl peroxide, lauroyl peroxide, di-t-butyl peroxide, t-butyl hydroperoxide, methyl ethyl ketone peroxide, and t-butyl perbenzoate. The catalysts may be used alone or in combination of two or more.

[0195] The composition of the present invention can also be cured by active energy rays. In this case, a photocationic polymerization initiator can be used as the polymerization initiator. The active energy rays can include visible light, ultraviolet light, X-rays, electron beams, etc.

[0196] Examples of the photocationic polymerization initiator include aryl-sulfonium salts and aryl-iodonium salts, and specifically, arylsulfonium hexafluorophosphate, arylsulfonium hexafluoroantimonate, arylsulfonium tetrakis(pentafluoro)borate, tri(alkylphenyl)sulfonium hexafluorophosphate, etc. The photocationic polymerization initiator may be used alone or in combination of two or more kinds.

[0197] <Laminate> The cured product of the present invention can be laminated with a substrate to form a laminate. The substrate of the laminate may be inorganic material such as metal or glass, or organic material such as plastic or wood, as appropriate for the application. The shape of the laminate may be flat, sheet-like, or may have a three-dimensional structure or may be solid. Any shape may be used depending on the purpose, such as one having curvature over the entire surface or a portion thereof. There are also no limitations on the hardness, thickness, etc. of the substrate. The cured product of the present invention may be used as a substrate, and further laminated with the cured product of the present invention.

[0198] Furthermore, a multilayer laminate may be obtained by laminating a substrate, a cured product layer, and a second substrate in this order. The resin composition of the present invention has excellent adhesive properties, and therefore can be suitably used as an adhesive for bonding a substrate and a second substrate.

[0199] The resin composition of the present invention has particularly high adhesion to metals and / or metal oxides, and therefore can be particularly well used as a primer for metals. Examples of metals include copper, aluminum, gold, silver, iron, platinum, chromium, nickel, tin, titanium, zinc, various alloys, and composite materials thereof, and examples of metal oxides include single oxides and / or composite oxides of these metals. Since the resin composition has particularly excellent adhesion to iron, copper, and aluminum, it can be particularly well used as an adhesive for iron, copper, and aluminum.

[0200] Furthermore, since the resin composition of the present invention can relieve stress, it is particularly suitable for use in bonding dissimilar materials. For example, even in a laminate in which the substrate is a metal and / or metal oxide and the second substrate is a dissimilar material such as a plastic layer, the adhesive strength is maintained due to the stress-relieving ability of the resin composition.

[0201] In the laminate of the present invention, the cured product layer may be formed by direct coating or molding on the substrate, or an already molded product may be laminated. When directly coating, the coating method is not particularly limited, and examples thereof include spraying, spin coating, dipping, roll coating, blade coating, doctor roll coating, doctor blade coating, curtain coating, slit coating, screen printing, and inkjet printing. When directly molding, examples thereof include in-mold molding, insert molding, vacuum molding, extrusion lamination molding, and press molding.

[0202] When laminating a molded resin composition, an uncured or semi-cured resin composition layer may be laminated and then cured, or a cured layer obtained by completely curing the composition may be laminated onto the substrate.

[0203] Alternatively, a precursor capable of serving as a substrate may be applied to the cured product of the present invention and cured to form a laminate, or the precursor capable of serving as a substrate or the composition of the present invention may be adhered in an uncured or semi-cured state and then cured. The precursor capable of serving as a substrate is not particularly limited, and examples thereof include various curable resin compositions.

[0204] <Fiber reinforced resin> When the resin composition of the present invention has a fibrous substrate and the fibrous substrate is a reinforcing fiber, the composition containing the fibrous substrate can be used as a fiber-reinforced resin. The method for incorporating a fibrous substrate into the composition is not particularly limited as long as it does not impair the effects of the present invention. Examples of methods include combining the fibrous substrate and the composition by kneading, coating, impregnation, injection, pressure bonding, etc., and this can be selected appropriately depending on the form of the fiber and the application of the fiber-reinforced resin.

[0205] The method for molding the fiber-reinforced resin of the present invention is not particularly limited. To produce a plate-shaped product, extrusion molding is commonly used, but flat presses are also possible. Other methods that can be used include extrusion molding, blow molding, compression molding, vacuum molding, and injection molding. To produce a film-shaped product, melt extrusion and solution casting can be used. Examples of melt molding methods include inflation film molding, cast molding, extrusion lamination molding, calendar molding, sheet molding, fiber molding, blow molding, injection molding, rotational molding, and coating molding. For resins that are cured with active energy rays, various curing methods using active energy rays can be used to produce cured products. In particular, when a thermosetting resin is used as the main component of the matrix resin, examples of molding methods include prepreg molding of the molding material and pressurizing and heating it using a press or autoclave. Other examples include RTM (Resin Transfer Molding), Vacuum-assisted Resin Transfer Molding (VaRTM), laminate molding, and hand layup molding.

[0206] <Prepreg> The fiber-reinforced resin of the present invention can be formed into a state called an uncured or semi-cured prepreg. After distributing the product in the prepreg state, final curing may be performed to form a cured product. When forming a laminate, it is preferable to form the prepreg, then laminate other layers, and then perform final curing, since this allows the formation of a laminate in which each layer is in close contact. The mass ratio of the composition and fibrous substrate used here is not particularly limited, but it is usually preferable to prepare the prepreg so that the resin content is 20 to 60 mass %.

[0207] <Heat-resistant materials and electronic materials> The resin composition of the present invention, when cured, has a high glass transition temperature and excellent thermal decomposition resistance, making it suitable for use in heat-resistant components. Furthermore, because it has excellent adhesion to substrates, it is particularly suitable for use in electronic components. It is particularly suitable for use in semiconductor encapsulants, circuit boards, build-up films, build-up boards, adhesives, and resist materials. It is also suitable for use as a matrix resin for fiber-reinforced resins, and is particularly suitable as a highly heat-resistant prepreg. The heat-resistant components and electronic components thus obtained can be used in a variety of applications, including, but not limited to, industrial machine parts, general machine parts, automobile, railway, and vehicle parts, aerospace and aviation-related parts, electronic and electrical components, building materials, containers and packaging materials, household goods, sports and leisure goods, and housing components for wind power generation.

[0208] Below, we will explain some representative products by giving examples.

[0209] 1.Semiconductor encapsulation materials A method for obtaining a semiconductor encapsulating material from the resin composition of the present invention includes thoroughly melt-mixing the resin composition, a curing accelerator, and compounding ingredients such as an inorganic filler, as needed, using an extruder, kneader, roll, or the like until homogeneous. In this process, fused silica is typically used as the inorganic filler. However, when used as a high-thermal-conductivity semiconductor encapsulating material for power transistors and power ICs, highly filled inorganic fillers such as crystalline silica, alumina, and silicon nitride, which have higher thermal conductivity than fused silica, or fused silica, crystalline silica, alumina, and silicon nitride may be used. The inorganic filler is preferably used in an amount of 30 to 95% by weight per 100 parts by weight of the curable resin composition. In particular, a filler content of 70 parts by weight or more is more preferred, and 80 parts by weight or more is even more preferred, in order to improve flame retardancy, moisture resistance, and solder crack resistance and to reduce the linear expansion coefficient.

[0210] 2. Semiconductor Devices A semiconductor package molding method for obtaining a semiconductor device from the curable resin composition of the present invention includes molding the semiconductor encapsulating material using a casting machine, a transfer molding machine, an injection molding machine, or the like, and then heating the molded product at 50 to 250°C for 2 to 10 hours.

[0211] 3. Printed Circuit Board A method for obtaining a printed circuit board from the composition of the present invention includes laminating the prepreg by a conventional method, appropriately overlaying copper foil, and heat-pressing the laminate under a pressure of 1 to 10 MPa at 170 to 300°C for 10 minutes to 3 hours.

[0212] 4. Build-up board A method for obtaining a build-up substrate from the composition of the present invention includes, for example, the following steps. First, the composition, which is appropriately blended with rubber, filler, and the like, is applied to a circuit board on which a circuit has been formed using a spray coating method, curtain coating method, or the like, and then cured (Step 1). Next, if necessary, predetermined through-holes or the like are drilled, the surface is treated with a roughening agent, and the surface is washed with hot water to form irregularities, followed by plating with a metal such as copper (Step 2). These operations are sequentially repeated as desired to alternately build up resin insulating layers and conductor layers of a predetermined circuit pattern (Step 3). Note that drilling of through-holes is performed after the formation of the outermost resin insulating layer. Alternatively, the build-up substrate of the present invention can be produced by forming a roughened surface by heat-pressing a copper foil, in which the resin composition has been semi-cured on a copper foil, onto a wiring board on which a circuit has been formed at 170 to 300°C, thereby eliminating the plating step.

[0213] 5. Build-up film A build-up film can be obtained from the composition of the present invention by applying the composition to the surface of a support film (Y) as a substrate, and then drying the organic solvent by heating or blowing hot air or the like to form a layer of the composition (X).

[0214] The organic solvent used here is preferably, for example, a ketone such as acetone, methyl ethyl ketone, or cyclohexanone; an acetate ester such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, or carbitol acetate; a carbitol such as cellosolve or butyl carbitol; an aromatic hydrocarbon such as toluene or xylene; dimethylformamide, dimethylacetamide, or N-methylpyrrolidone; and it is preferably used in a proportion such that the nonvolatile content is 30 to 60% by mass.

[0215] The thickness of the layer (X) formed is usually equal to or greater than the thickness of the conductor layer. Since the thickness of the conductor layer of a circuit board is usually in the range of 5 to 70 μm, the thickness of the resin composition layer is preferably 10 to 100 μm. In addition, the layer (X) of the composition in the present invention may be protected with a protective film described below. Protection with a protective film can prevent adhesion of dust and the like to the surface of the resin composition layer and scratches.

[0216] Examples of the support film and protective film include polyolefins such as polyethylene, polypropylene, and polyvinyl chloride; polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate; polycarbonate; polyimide; and even release paper and metal foils such as copper foil and aluminum foil. The support film and protective film may be subjected to a matte treatment, corona treatment, or release treatment. The thickness of the support film is not particularly limited, but is usually 10 to 150 μm, and preferably 25 to 50 μm. The thickness of the protective film is preferably 1 to 40 μm.

[0217] The support film (Y) is peeled off after laminating it onto a circuit board or after forming an insulating layer by heat curing. If the support film (Y) is peeled off after the curable resin composition layer constituting the build-up film is heat cured, adhesion of dust and the like during the curing process can be prevented. When peeling off after curing, the support film is usually subjected to a release treatment in advance.

[0218] A multilayer printed circuit board can be produced using the build-up film obtained as described above. For example, if the layer (X) is protected by a protective film, the film is peeled off, and then the layer (X) is laminated to one or both sides of the circuit board so as to be in direct contact with the circuit board, for example, by a vacuum lamination method. The lamination method may be a batch method or a continuous method using a roll. If necessary, the build-up film and the circuit board may be heated (preheated) before lamination. The lamination conditions are preferably a pressure bonding temperature (lamination temperature) of 70 to 140°C and a pressure bonding pressure of 1 to 11 kgf / cm. 2 (9.8×10 4 ~107.9×10 4 N / m 2 ), and lamination is preferably carried out under reduced air pressure of 20 mmHg (26.7 hPa) or less.

[0219] 6.Conductive paste A method for obtaining a conductive paste from the composition of the present invention includes, for example, dispersing conductive particles in the composition. Depending on the type of conductive particles used, the conductive paste can be a paste resin composition for circuit connection or an anisotropic conductive adhesive. [Example]

[0220] The present invention will now be described in more detail with reference to examples and comparative examples, in which "parts" and "%" are by mass unless otherwise specified.

[0221] 1 H and 13 C-NMR, FD-MS spectrum, and GPC were measured under the following conditions.

[0222] 1 H-NMR: “JNM-ECA600” manufactured by JEOL RESONANCE Magnetic field strength: 600MHz Accumulation count: 32 times Solvent: DMSO-d6 Sample concentration: 30% by mass

[0223] 13 C-NMR: “JNM-ECA600” manufactured by JEOL RESONANCE Magnetic field strength: 150MHz Accumulation count: 320 times Solvent: DMSO-d6 Sample concentration: 30% by mass

[0224] FD-MS: JEOL Ltd. "JMS-T100GC AccuTOF" Measurement range: m / z = 50.00 to 2000.00 Rate of change: 25.6mA / min Final current value: 40mA Cathode voltage: -10kV

[0225] GPC: Tosoh Corporation "HLC-8320GPC" Column: Tosoh Corporation "TSK-GEL G2000HXL" + "TSK-GEL G3000HXL" + "TSK-GEL G4000HXL" Detector: RI (differential refractometer) Measurement conditions: 40°C Mobile phase: tetrahydrofuran Flow rate: 1ml / min Standard: Tosoh Corporation "PStQuick A", "PStQuick B", "PStQuick E", "PStQuick F"

[0226] The epoxy equivalent of the synthesized epoxy resin was measured in accordance with JIS K7236, and the epoxy equivalent (g / eq) was calculated.

[0227] Examples of methods for calculating the number of repeating units include calculation from the results of GPC molecular weight measurement, and various appropriate instrumental analyses such as FD-MS and NMR.

[0228] [Synthesis Example 1] A flask equipped with a thermometer and stirrer was charged with 136 g (0.43 mol) of diglycidyl ether of 1,6-hexanediol ("SR-16H" manufactured by Sakamoto Pharmaceuticals; epoxy equivalent: 160 g / eq), 66 g (0.07 mol) of diglycidyl ether of polytetramethylene glycol ("Denacol EX-991L" manufactured by Nagase ChemteX; epoxy equivalent: 445 g / eq), and 119.7 g (0.53 mol) of bisphenol A (hydroxyl equivalent: 114 g / eq). The mixture was heated to 140 °C over 30 minutes, and then 3.2 g of 20% aqueous sodium hydroxide solution was added. The mixture was then heated to 150 °C over 30 minutes and allowed to react at 150 °C for 20 hours. A neutralizing amount of sodium phosphate was then added, yielding 320 g of the hydroxy compound (Ph-1). This hydroxy compound (Ph-1) was confirmed to contain the target hydroxy compound because a peak of M+ = 1839 was obtained in the mass spectrum, which corresponds to the theoretical structure of n1 = 6, m1 = 1, n2 = 11, and m2 = 1 in the structural formula (Ph-1). The hydroxyl equivalent weight of this hydroxy compound (Ph-1) calculated by GPC was 1896 g / eq.

[0229] [ka]

[0230] [Synthesis Example 2] A flask equipped with a thermometer and a stirrer was charged with 126.2 g (0.39 mol) of diglycidyl ether of 1,6-hexanediol ("SR-16H" manufactured by Sakamoto Pharmaceuticals; epoxy equivalent: 160 g / eq), 78.1 g (0.08 mol) of diglycidyl ether of polypropylene glycol ("Denacol EX-931" manufactured by Nagase ChemteX; epoxy equivalent: 481 g / eq), and 114.6 g (0.50 mol) of bisphenol A (hydroxyl equivalent: 114 g / eq). The mixture was heated to 140 °C over 30 minutes, and then 3.2 g of 20% aqueous sodium hydroxide solution was added. The subsequent operations were the same as in Synthesis Example 1, and 317 g of the hydroxy compound (Ph-2) was obtained. This hydroxy compound (Ph-2) was confirmed to contain the target hydroxy compound because a peak at M+ = 1684 was confirmed in the mass spectrum, which corresponds to the theoretical structure of n1 = 6, m1 = 1, n2 = 11, and m2 = 1 in the structural formula (Ph-2). The hydroxyl equivalent weight of this hydroxy compound (Ph-2) calculated by GPC was 1597 g / eq.

[0231] [ka]

[0232] [Synthesis Example 3] A flask equipped with a thermometer and stirrer was charged with 179 g (0.56 mol) of diglycidyl ether of 1,6-hexanediol ("SR-16H" manufactured by Sakamoto Pharmaceuticals; epoxy equivalent: 160 g / eq) and 133.6 g (0.59 mol) of bisphenol A (hydroxyl equivalent: 114 g / eq). The temperature was raised to 140 °C over 30 minutes, and then 3.2 g of 20% aqueous sodium hydroxide solution was added. The subsequent reaction procedures were the same as in Synthesis Example 1, yielding 305 g of hydroxy compound (Ph-2). This hydroxy compound (Ph-3) was confirmed to contain the desired hydroxy compound by mass spectrometry, which confirmed a peak at M+ = 687, corresponding to the theoretical structure of n1 = 6, m1 = 1 in the structural formula (Ph-3). The hydroxyl equivalent of this hydroxy compound (Ph-3) was calculated to be 2244 g / eq by GPC.

[0233] [ka]

[0234] [Synthesis Example 4] A flask equipped with a thermometer and stirrer was charged with 195 g (0.22 mol) of polytetramethylene glycol diglycidyl ether (Nagase ChemteX "Denacol EX-991L": epoxy equivalent 445 g / eq) and 59.9 g (0.26 mol) of bisphenol A (hydroxyl equivalent 114 g / eq). The temperature was raised to 140 °C over 30 minutes, and then 2.5 g of 20% aqueous sodium hydroxide solution was added. The subsequent reaction procedures were the same as in Synthesis Example 1, yielding 250 g of hydroxy compound (Ph-4). This hydroxy compound (Ph-4) was confirmed to contain the desired hydroxy compound by mass spectrometry, which confirmed a peak at M+ = 1380, corresponding to the theoretical structure of structural formula (Ph-4) with M = 1, n2 = 11, and m2 = 1. The hydroxyl equivalent of this hydroxy compound (Ph-4) was calculated to be 2497 g / eq by GPC.

[0235] [ka]

[0236] [Synthesis Example 5] A flask equipped with a thermometer and stirrer was charged with 230.9 g (0.24 mol) of polypropylene glycol diglycidyl ether (Nagase ChemteX "Denacol EX-931": epoxy equivalent 481 g / eq) and 65.7 g (0.29 mol) of bisphenol A (hydroxyl equivalent 114 g / eq). The temperature was raised to 140 °C over 30 minutes, and then 3.0 g of 20% aqueous sodium hydroxide solution was added. The subsequent reaction procedures were the same as in Synthesis Example 1, yielding 290 g of hydroxy compound (Ph-5). This hydroxy compound (Ph-5) was confirmed to contain the desired hydroxy compound by mass spectrometry, which confirmed a peak at M+ = 1226, corresponding to the theoretical structure of n2 = 11 and m2 = 1 in the structural formula (Ph-5). The hydroxyl equivalent of this hydroxy compound (Ph-5) was calculated to be 1447 g / eq by GPC.

[0237] [ka]

[0238] [Example 1] A flask equipped with a thermometer, dropping funnel, condenser, and stirrer was purged with nitrogen gas. 200 g of the hydroxy compound Ph-1 obtained in Synthesis Example 1, 437 g (4.72 mol) of epichlorohydrin, and 118 g of n-butanol were charged and dissolved. After heating to 65°C, the pressure was reduced to an azeotropic pressure, and 6.66 g (0.08 mol) of 49% aqueous sodium hydroxide solution was added dropwise over 5 hours. Stirring was then continued under the same conditions for 0.5 hours. During this time, the azeotropically distilled fraction was separated using a Dean-Stark trap, the aqueous layer was removed, and the oil layer was returned to the reaction system while the reaction was continued. Unreacted epichlorohydrin was then removed by vacuum distillation. 150 g of methyl isobutyl ketone and 150 g of n-butanol were added to the resulting reaction mixture and dissolved. This solution was then mixed with 10g of 10% aqueous sodium hydroxide and reacted at 80°C for 2 hours. The mixture was then washed three times with 100g of water until the pH of the wash solution became neutral. The system was then dehydrated by azeotropy, and after microfiltration, the solvent was removed under reduced pressure to yield 190g of epoxy resin Ep-1. The resulting epoxy resin Ep-1 had an epoxy equivalent of 2167g / eq. Mass spectrometry revealed a peak at M+ = 1951, corresponding to the theoretical structure of the structural formula (Ep-1) below: m1 = 1, n1 = 6, m2 = 1, n2 = 11, q = 1, p1 = 0, p2 = 0. This confirmed the presence of the desired epoxy resin Ep-1.

[0239] [ka]

[0240] [Example 2] The same reaction as in Example 1 was carried out, except that 200 g of the hydroxy compound Ph-1 obtained in Synthesis Example 1 was replaced with 200 g of the hydroxy compound Ph-2 obtained in Synthesis Example 2, to obtain 190 g of epoxy resin Ep-2. The epoxy equivalent of the obtained epoxy resin Ep-2 was 1835 g / eq. Mass spectrometry of this epoxy resin Ep-2 showed a peak at M+ = 1796, which corresponds to the theoretical structure of the following structural formula (Ep-2): m1 = 1, n1 = 6, m2 = 1, n2 = 11, q = 1, p1 = 0, p2 = 0, confirming that this epoxy resin Ep-2 contained the target epoxy resin Ep-2.

[0241] [ka]

[0242] [Synthesis Example 6] The same reaction as in Example 1 was carried out, except that 200 g of the hydroxy compound Ph-1 obtained in Synthesis Example 1 was replaced with 200 g of the hydroxy compound Ph-3 obtained in Synthesis Example 3, to obtain 190 g of epoxy resin Ep-3. The epoxy equivalent of the obtained epoxy resin Ep-3 was 2244 g / eq. Mass spectrometry of this epoxy resin Ep-3 showed a peak at M+ = 799, which corresponds to the theoretical structure of the following structural formula (Ep-3) where m1 = 1, n1 = 6, q = 1, p1 = 0, and p2 = 0, confirming that it contained the target epoxy resin Ep-3.

[0243] [ka]

[0244] [Synthesis Example 7] The same reaction as in Example 1 was carried out, except that 200 g of the hydroxy compound Ph-1 obtained in Synthesis Example 1 was replaced with 200 g of the hydroxy compound Ph-4 obtained in Synthesis Example 4, to obtain 185 g of epoxy resin Ep-4. The epoxy equivalent of the obtained epoxy resin Ep-4 was 2834 g / eq. Mass spectrometry of this epoxy resin Ep-4 showed a peak at M+ = 1492, which corresponds to the theoretical structure of the following structural formula (Ep-4) where m2 = 1, n2 = 11, q = 1, p1 = 0, and p2 = 0, confirming that it contained the desired epoxy resin Ep-4.

[0245] [ka]

[0246] [Synthesis Example 8] The same reaction as in Example 1 was carried out, except that 200 g of the hydroxy compound Ph-1 obtained in Synthesis Example 1 was replaced with 200 g of the hydroxy compound Ph-5 obtained in Synthesis Example 5, to obtain 190 g of epoxy resin Ep-5. The epoxy equivalent of the obtained epoxy resin Ep-5 was 1668 g / eq. Mass spectrometry of this epoxy resin Ep-) showed a peak at M+ = 1338, which corresponds to the theoretical structure of the following structural formula (Ep-5) where m2 = 1, n2 = 11, q = 1, p1 = 0, and p2 = 0, confirming that it contained the target epoxy resin Ep-5.

[0247] [ka]

[0248] [Examples 3 to 6 and Comparative Examples 1 to 3] Preparation of Compositions and Cured Resins An epoxy resin composition was obtained by uniformly mixing epoxy resin, curing agent (1.0 equivalent relative to the epoxy), curing accelerator (0.85 parts by weight relative to the epoxy) and filler (light calcium carbonate, Omi Chemical Industry Co., Ltd.) in a mixer (Thinky Corporation's "Awatori Rentaro ARV-200") according to the formulations shown in Tables 1 and 2. This epoxy resin composition was sandwiched between aluminum mirror plates (Engineering Test Service Co., Ltd.'s "JIS H 4000 A1050P") using a silicone tube as a spacer and heat-cured at 170°C for 30 minutes to obtain a 0.8 mm-thick cured resin.

[0249] <Glass transition temperature> The 0.8 mm thick cured product was cut into a size of 5 mm wide and 40 mm long, and this was used as a test specimen. This test specimen was measured using a viscoelasticity measuring device (DMA: Hitachi High-Tech Science Corporation, solid viscoelasticity measuring device "DMS7100", deformation mode: tension, measurement mode: sinusoidal vibration, frequency: 1 Hz, heating rate: 3 °C / min), and the temperature at which the change in elastic modulus was greatest (the rate of change in tan δ was greatest) was evaluated as the glass transition temperature. Note that when multiple peak tops were present, they were listed in the table as multiple glass transition temperatures.

[0250] <Tensile test> The cured resin was punched into a dumbbell shape (JIS K 7161-2-1BA) using a punching blade to prepare a test specimen. The test specimen was subjected to a tensile test in accordance with JIS K 7162-2 using a Shimadzu Autograph AG-IS tester at 23°C (test speed: 2 mm / min).

[0251] <Tensile shear test> The resin composition was applied to one of two cold-rolled steel sheets (SPCC-SB manufactured by TP Giken Co., Ltd., 1.0 mm × 25 mm × 100 mm), glass beads (J-80 manufactured by Potters Barottini Co., Ltd.) were added as spacers, and the other SPCC-SB was bonded (bonding area: 25 mm × 12.5 mm). This was heat-cured at 170 °C for 30 minutes to obtain test pieces. The adhesiveness was evaluated by performing a tensile shear test using the test pieces. The test was conducted according to JIS K 6850, and the maximum point stress at measurement environments of -40 °C, 23 °C, and 80 °C was compared.

[0252] <T-peel test> The resin composition was applied to one of two cold-rolled steel sheets (SPCC-SB manufactured by TP Giken Co., Ltd., 0.5 mm × 25 mm × 200 mm), glass beads (J-80 manufactured by Potters Barottini Co., Ltd.) were added as spacers, and the other SPCC-SB was bonded (bonding area: 25 mm × 150 mm). This was heat-cured at 170 °C for 30 minutes to obtain test pieces. The adhesiveness was evaluated by performing a T-peel test using the test pieces. The test was conducted according to JIS K 6854-3, and the average stress at measurement environments of -40 °C, 23 °C, and 80 °C was compared.

[0253] <Observation of phase separation structure> Cross-sections of the cured resin were prepared with an ultramicrotome, and the phase separation structure was observed. The observation method was carried out using a scanning electron microscope (SEM) and an atomic force microscope (AFM). By SEM observation, the presence or absence of the phase separation structure in the cured product can be confirmed. When the cured product has a phase separation structure and the structure forms a sea-island structure, the particle size of the island part was measured. Regarding the average value of the particle size, 50 island parts were randomly extracted from the island parts within a field of view of 200 μm × 260 μm to measure the particle size, and the average particle size was obtained. Also, from AFM observation, the relative hardness distribution of the sea part and the island part can be confirmed.

[0254] (SEM) Model used: JSM-7800F manufactured by JEOL Ltd., Accelerating voltage: 5 kV

[0255] (AFM) Model used: Bruker AXS NANO Scope (R) IIIa Measurement mode: DFM Cantilever: Si-DF20 Measurement image type: Topographic image, phase image

[0256] [Table 1]

[0257] [Table 2]

[0258] The materials used in the table are as follows: E-850S: Bisphenol A epoxy resin (DIC Corporation, epoxy equivalent weight 188g / eq) CaCO3: Light calcium carbonate (Omi Chemical Industry Co., Ltd.) DICY: Dicyandiamide ("DICY7" manufactured by Mitsubishi Chemical Corporation) DCMU: 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DIC Corporation, "B-605-IM")

[0259] As shown in Examples 3 to 6, it is clear that the present invention has a high elongation rate in the tensile test and excellent adhesiveness over a wide temperature range. [Industrial Applicability]

[0260] The epoxy resin of the present invention can provide a flexible cured product that combines high elongation assuming elastic deformation with high adhesiveness that can withstand the difference in thermal expansion of the substrate. In particular, the resin composition obtained from epoxy resin A and epoxy resin B of the present invention has a phase-separated structure after curing that achieves both adhesiveness and stress relaxation ability in the cured product, making it suitable for use in adhesives for structural materials and advanced electronic materials such as semiconductor encapsulation materials and insulating layers for multilayer printed circuit boards.

Claims

1. The following general formula (1) 【Chemistry 1】 [In formula (1), each Ar is independently a structure having an unsubstituted or substituted aromatic ring, X is a structural unit represented by the following general formula (2), and Y is a structural unit represented by the following general formula (3): 【Chemistry 2】 [In the formulas (2) and (3), Ar is the same as defined above, R 1 , R 2 each independently represents a hydrogen atom, a methyl group, or an ethyl group, R' is a divalent hydrocarbon group having 2 to 12 carbon atoms; R 3 , R 4 , R 7 , R 8 each independently represents a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group, R 5 , R 6 , R 9 , R 10 each independently represents a hydrogen atom or a methyl group, n1 is an integer from 4 to 16, n2 is the average number of repeating units and is from 2 to 30. R 11 , R 12 each independently represents a glycidyl ether group or a 2-methylglycidyl ether group, R 13 , R 14 each independently represents a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group, R 15 , R 16 is a hydrogen atom or a methyl group, p1, p2, and q are the average values ​​of the repetitions, p1 and p2 each independently represent 0 to 5; and q is 0.5 to 5. However, the bond between X represented by the general formula (2) and Y represented by the general formula (3) may be random or block, and the total numbers of the structural units X and Y present in one molecule are m1 and m2, respectively. An epoxy resin represented by the formula: Epoxy resin (a1) in which 1≦m1≦25 and 1≦m2≦25; or An epoxy resin (A) having an epoxy equivalent of 500 to 10,000 g / eq, comprising, as essential components, an epoxy resin (a2) satisfying 1≦m1≦25 and m2=0, and an epoxy resin (a3) ​​satisfying m1=0 and 1≦m2≦25; An epoxy resin (B) having an epoxy equivalent of 100 to 300 g / eq; An epoxy resin composition comprising:

2. Ar in the general formulas (1) to (3) is each independently represented by the following structural formula (4): 【Chemistry 3】 ・・・(4) (The aromatic ring in formula (4) may be substituted or unsubstituted, and * represents a point of attachment.) 2. The epoxy resin composition according to claim 1, wherein the epoxy resin composition is any one of the following:

3. In the general formula (2), n1 is 6 to 12, and R 3 and R 4 is a hydroxyl group, R 5 and R 6 3. The epoxy resin composition according to claim 1 or 2, wherein is a hydrogen atom.

4. In the general formula (3), R' is a divalent hydrocarbon group having 2 to 6 carbon atoms, and R 7 and R 8 is a hydroxyl group, R 9 and R 10 The epoxy resin composition according to any one of claims 1 to 3, wherein is a hydrogen atom.

5. 5. The epoxy resin composition according to claim 1, wherein the epoxy equivalent of the epoxy resin (A) is in the range of 800 to 5000 g / eq.

6. 6. The epoxy resin composition according to claim 1, wherein, in formula (1), Ar further has a glycidyl ether group and / or a 2-methylglycidyl ether group.

7. The epoxy resin composition according to any one of claims 1 to 6, wherein a mass ratio (A):(B) of the epoxy resin (A) to the epoxy resin (B) is 90:10 to 10:

90.

8. The epoxy resin composition according to any one of claims 1 to 7, further comprising a curing agent (C).

9. The epoxy resin composition according to any one of claims 1 to 8, which is an adhesive.

10. A cured product of the epoxy resin composition according to any one of claims 1 to 9.

11. the cured product has a phase-separated structure consisting of resin particles having an average particle size of 10 nm to 100 μm and a matrix surrounding the resin particles, The cured product according to claim 10 , wherein the resin particles contain a cured product of the epoxy resin (A), and the matrix contains a cured product of the epoxy resin (B).

12. the cured product has a phase-separated structure consisting of resin particles having an average particle size of 10 nm to 100 μm and a matrix surrounding the resin particles, The cured product according to claim 10 , wherein the resin particles contain a cured product of the epoxy resin (B), and the matrix contains a cured product of the epoxy resin (A).

13. A laminate comprising a substrate and the cured product according to any one of claims 10 to 12 laminated thereon.

14. The laminate according to claim 13, which is obtained by laminating in this order a first substrate, a layer made of the cured product according to any one of claims 10 to 12, and a second substrate.

15. 15. The laminate according to claim 14, wherein the first substrate is a substrate made of a metal or a metal oxide, and the second substrate is a substrate made of a plastic.

16. The following general formula (5) 【Chemistry 4】 In formula (5), each Ar is independently a structure having an unsubstituted or substituted aromatic ring, X is a structural unit represented by the following general formula (2), and Y is a structural unit represented by the following general formula (3): 【Chemistry 5】 [In the formulas (2) and (3), Ar is the same as defined above, R 1 , R 2 each independently represents a hydrogen atom, a methyl group, or an ethyl group, R' is a divalent hydrocarbon group having 2 to 12 carbon atoms; R 3 , R 4 , R 7 , R 8 each independently represents a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group, R 5 , R 6 , R 9 , R 10 each independently represents a hydrogen atom or a methyl group, n1 is an integer from 4 to 16, n2 is the average number of repeating units and is from 2 to 30. R 11 , R 12 each independently represents a glycidyl ether group or a 2-methylglycidyl ether group, R 13 , R 14 each independently represents a hydroxyl group, a glycidyl ether group, or a 2-methylglycidyl ether group, R 15 , R 16 is a hydrogen atom or a methyl group, p1, p2, and q are the average values ​​of the repetitions, p1 and p2 each independently represent 0 to 5; and q is 0.5 to 5. However, the bond between X represented by the general formula (2) and Y represented by the general formula (3) may be random or block, and the total numbers of the structural units X and Y present in one molecule are m1 and m2, respectively. An epoxy resin represented by the formula: An epoxy resin characterized in that 1≦m1≦25 and 1≦m2≦25, and that the epoxy equivalent is 500 to 10,000 g / eq.

Citation Information

Patent Citations

  • Preparation of epoxy resin

    JP1980161817A

  • New low-viscosity linear glycidyl ethers, their production and epoxy resin composition containing the same

    JP1995278129A

  • Brominated epoxy resin composition for laminate

    JP1996053533A

  • Epoxy resin composition, its cured product, novel hydroxy compound, novel epoxy resin and manufacturing method of these

    JP2006335796A

  • Composition, and composition sheet comprising the same

    JP2011046928A